Master teachers as teacher leaders: evidence from Malaysia and the Philippines - Bush, Tony; Glover, Derek; Ng, Ashley Yoon Moi; Romero, Mary-Jean (Commonwealth Council for Educational Administration and Management, 2016)
The career paths of teachers in most countries lead to talented practitioners progressively reducing their classroom work to take on leadership and management responsibilities culminating in headship. Some education systems seek to keep good teachers in classrooms by offering alternative promoted posts, often described as master teachers. This article presents evidence of the role of master teacher in two underpublished Asia-Pacific contexts: Malaysia and the Philippines. Drawing on interviews with master teachers, and their principals and colleagues, the article provides a picture of the activities and role relationships of these senior practitioners. The findings show that the master teacher role largely succeeds in keeping talented and ambitious teachers in the classroom, but there is only limited evidence of a wider impact on colleagues, schools and the education system.